Analysis of Health Istitha'ah For the Postponement of The Departure of Hajj Pilgrims According to The Perspective of Fiqh Siyasah - Diki Ardian Saputra; Muhammad Mahmud Nasution (Warmadewa Press, 2024)
The Indonesian government has made health istitha'ah a mandatory condition for the Hajj pilgrimage. On January 9, 2024, the government updated the regulations concerning health istitha'ah, making it a prerequisite for the repayment of BIPIH (Hajj costs). This research uses normative research methods or library research from various trusted sources. The results of this research show that the government made changes to regulations because many Indonesian Hajj pilgrims died in the holy land in the past, and it is hoped that this change can prevent Hajj pilgrims from dying. This new regulation is not intended to make things difficult for Hajj pilgrims, their departure will only be postponed and put back in the queue, and if the following year they have recovered, they can depart. According to Siyasah Fiqh, this change is good, because it prioritizes the safety of the Hajj pilgrims. Apart from that, this decision is also in line with the rules in Al-Darurah Fiqh, namely, avoiding damage takes priority over achieving benefit.